ANALYSIS OF LEAD, COPPER AND ZINC CONCENTRATIONS IN FLESH AND SHELL OF SNAIL Litoraria melanostoma IN THE WEST COAST OF KARIMUN BESAR ISLAND OF RIAU ISLANDS - Pesta Martua Sirait; Bintal Amin; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in February 2015 to determine the concentration of heavy metals (Pb, Cu and Zn) in the flesh and shell of snail L. melanostoma collected from the west coast of Karimun Besar Island of Riau Islands Province. The differences in metal concentrations between shell and flesh as well as between stations were discussed. Higher concentrations of Pb and Cu were found in the flesh, whilst zinc concentration was found to be higher in the shell of the snail. The highest Pb concentration was found in Station I (8.105 μg/g) and the lowest was in Station III (6.476 μg/g). The highest Cu concentration was found in Station II (5.193 μg/g) and the lowest was in Station III (4.333 μg/g). Meanwhile the highest Zn concentration was found in Station III (7.675 μg/g) and the lowest was in Station II (7.408 μg/g). The MPI value of the metals in the west coast of Karimun Besar Island still quite low when compared with other reported regional studies. Keywords: Lead, Copper, Zinc, snail, shell, flesh, Karimun